Switzerland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix evaluates Switzerland's long-term growth and productivity performance. It analyzes the behavior of Swiss fiscal policy over the business cycle and takes a fresh look at the nature of the tradeoff between inflation and economic activity in Switzerland. The paper reports estimates of the automatic and discretionary responses of general government finances to cyclical output movements during 1970-96. It also examines the main options for improving the stabilization role of Switzerland's fiscal policy over the business cycle.